(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
We develop and analyze a distributed space-frequency block code-orthogonal frequency division multiplexing protocol for cooperative communications in 802.11 networks. Space frequency block codes (SFBC) are spread over OFDM subcarriers instead of OFDM symbols to compensate for the small coherence time. Medium access control (MAC) layer packet retransmission limit has been used as an actuator for transmit cooperative diversity initialization. Transmit diversity is provided by the relays in close proximity to source node. Closed form expressions are obtained for packet error rate (PER) and average delay for the proposed scheme in Nakagami-m fading channels. This cooperative scheme achieves lower signal-to-noise ratio (SNR) values for desired packet error rate and markedly improves the average delay per packet compared to the direct transmissions at low SNR regime. Finally, the results of computer simulations are included to demonstrate the efficacy of the proposed scheme and to verify the accuracy of analytical expressions.